Conservation and Development of Hakka Mountain Songs for Cultural Inheritance - Bian, Xiumei; Pikulsri, Chalermsak (Journal of Fine and Applied Arts Khon Kaen University, 2020)
Hakka mountain songs are an artistic performance and an important cultural heritage of the Chinese that are in need of conservation, revitalization, and development. Current difficulties for Hakka mountain songs are 1) Changing society and the environment, 2) Lack of audience and inheritors, 3) Lack of innovation, 4) The impact of Multiculturalism. The conservation and development of Hakka mountain songs can be helped by 1) Collecting and maintaining the documents of Hakka mountain songs. 2) The use of a national policy to build the establishment of an inheritance mechanism. 3) Construction of Hakka mountain songs brand. 4) Innovation of Hakka mountain songs based on the characteristics of the times. 5) Music education is the basis for the development of Hakka mountain songs.